2019
DOI: 10.1194/jlr.m089300
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic VLDL secretion: DGAT1 determines particle size but not particle number, which can be supported entirely by DGAT2

Abstract: We investigated whether, in view of its activity being expressed on both aspects of the endoplasmic reticulum (ER; dual membrane topology), diacylglycerol acyltransferase 1 (DGAT1) plays a distinctive role in determining the triglyceride (TAG) content of VLDL particles secreted by the liver. Mice in which the DGAT1 gene was specifically ablated in hepatocytes (DGAT1-LKO mice) had the same number of VLDL particles (apoB concentration) in the plasma 1 h after Triton 1339 treatment, but these particles were appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…In contrast, DGAT2 is localized in the ER and around LDs and is specialized in LDs. 44 Our data demonstrated that the expression of DGAT1 and 2 was significantly increased in hearts of db/db mice. Some studies have confirmed that LDs increased in abundance where UPR is activated.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, DGAT2 is localized in the ER and around LDs and is specialized in LDs. 44 Our data demonstrated that the expression of DGAT1 and 2 was significantly increased in hearts of db/db mice. Some studies have confirmed that LDs increased in abundance where UPR is activated.…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported that DGAT1 participates in VLDL secretion, with one study showing that DGAT1 overexpression in mouse liver increased VLDL secretion 39 and the other showing that DGAT1 is involved in lipidation and maturation of hepatic VLDL particles. 32 Our fast protein liquid chromatography and immunoblot analysis results suggest that DGAT1 may be involved in VLDL lipidation and secretion because DGAT1 deletion resulted in a decrease of serum VLDL-TG levels as well as ApoB100 protein levels after alcohol feeding. Thus, DGAT1-mediated VLDL secretion of TG is an adaptive response to the increased exogenous FFAs influx to the liver.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, directing TG as Mttp substrate away from lumenal LDs may reduce Mttp transcription and, consequently, influence the expression of cholesterol transporters. VLDL particle size was also reduced in hepatocyte-specific Dgat1 −/− mice [ 34 ], indicating that Dgat1 is critical for the size of ApoB-containing lipoproteins. Unaltered cholesterol content in VLDL of these mice is in line with differently regulated cholesterol incorporation into ApoB-containing lipoproteins of hepatocytes and enterocytes, since in enterocytes this process is largely dependent on TG incorporation into CMs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%